HIDUP DALAM KERAGAMAN: MASALAH DAN WAWASAN KERAGAMAN - Ludji, Barnabas (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2019)
As God's people, the church needs to realize that diversity is an essential nature of the Unitary State of the Republic of Indonesia. Efforts to homogenize nations that are diverse in race, ethnicity, culture, and religion must be seen as efforts to divide the nation. Therefore religions in Indonesia, especially the Church of God must really be a motivator and encourage their citizens to be truly aware of the diversity of the nation and take part in fostering a lifeof life that respects diversity and tolerates life with fellow human beings with everything attached to himself, including his religion and culture. In connection with the above, the church leaders and theologians must really try to find an understanding of faith that encourages people to accept differences and be able to build a tolerant life together. Efforts in that direction can be built through the perspectives of all fields of theological studies. This paper contains efforts to build a tolerant shared life from a systematic perspective. Theology of Religions and the Biblical (Old Testament). The dogmaticperspective sees two basic needs, namely to nurture and increasingly take root in the faith of church members, and the need to determine attitudes towards the presence of other religious life together. Without forgetting the universal nature of religion as an expression of religious awareness. From an ethical perspective feel the need to develop global ethics that are universal. From the perspective of the science of religions, it is necessary to highlight the verses of the Scriptures possessed by each religion that is universal. While the Biblical perspective sees the importance of Christians understanding their holy books diachronically and holistically. Because improper ways of understanding the Bible make possible the birth of exclusive fundamentalists. Central themes, such as love, justice, truth, peace, redemption, goodness, and life are believed to be from God, all of which are universal. All biblical texts, if understood, diachronically, then the text messages are the central themes already mentioned.